Hadis-hadis Tanawu' al-IBadah (Kajian tentang Berbagai Cara Pelaksanaan Ibadah Shalat Dalam Perspektif Hadis Nabi Muhammad Saw.) - Nurlizam Nurlizam (Alhurriyah, 2013)
Hadiths tanawu `al-worship are hadiths that explain certain religious practices conducted or taught the Prophet Muhammad, but from each other so that there is a difference illustrates the diversity of the teachings in the implementation of the worship. Differences or religious doctrine is sometimes in the form of implementing procedures (actions) and sometimes in the form of words or passages that are read by the Prophet Muhammad in worship. If all tanawu `al-hadith is considered acceptable worship and that there is a difference between one and the other does not lead to conflict that can not be compromised, then the hadith must be received and acknowledged his position to be practiced. The teachings were brought to be understood as a means or other forms of execution, or the various forms of literature, which may be followed and practiced, and which of them is selected, it has qualified for the worship syahnya. It contains wisdom that the teachings of Islam’s Agana Lues and always makes it easy for people.